Թուրքիայի քաղաքական ընտրանու բնորոշ գծերը (1920-1930 թթ.) - Բաղդասարյան, Սուրեն («Զանգակ - 97»)
The mechanism of the political power in cvery State works through its major actors - the political parties, political leaders and political elite. In 1920-1930s in Turkey there was a need to form a new political elite. The main componcnts of the Turkish political elite were the military, State bureaucracy, urban intellectuals as well as the representatives of Anatolian local elite and clericals. It was divided into several groups - the associates of the President of the Republic, members of the government and the ruling organs of Republican People Party, Ihe deputies of mejlis, the Commanders of the army, the vilayets' govemors.
Keywords: Պատմություն; Քաղաքականություն; Թուրքիա